Konstruksi Hukum Kewenangan Penyidik terhadap Aset Debitur Pailit dalam Perkara Tindak Pidana Pencucian Uang - Afrizal Evaldo Maulana; Made Warka (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Conflicts of jurisdiction between investigators and trustees frequently arise when assets that have become part of the bankruptcy estate are suspected of being derived from money laundering offences and are subject to seizure in criminal proceedings. Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering grants investigators the authority to trace and seize assets derived from criminal offences through a ‘follow the money’ approach. At the same time, Law No. 37 of 2004 on Bankruptcy and the Suspension of Debt Payment Obligations places all the assets of a bankrupt debtor under general attachment, which are under the control and administration of the trustee. These differing provisions give rise to a lack of harmonisation of legal norms and legal uncertainty regarding the limits of investigators’ authority over the assets of a debtor who has been declared bankrupt. This study aims to analyse the legal framework of the investigator’s authority over the assets of a bankrupt debtor in money laundering criminal cases. The research method employed is normative legal research using a statutory approach, a conceptual approach, and a case approach. The legal material was analysed qualitatively using legal interpretation methods to identify the relationship between the criminal law regime and bankruptcy law. The research findings indicate that the investigator’s authority to seize assets derived from criminal offences is an attributive power conferred by law; however, its application to the bankruptcy estate has not been explicitly regulated, thereby potentially giving rise to conflicts of authority with the trustee. An ideal legal framework would allow criminal seizure to continue to be carried out against assets suspected of being derived from criminal offences, whilst still observing the principles of coordination, notification to the trustee, and protection of creditors’ interests. This model is expected to create harmony between the criminal law regime and the insolvency law regime and provide legal certainty for all interested parties.